Factors associated with lifestyle and diet in heart failure mortality - Lau, Cheng Cheng (2022)
With the expansion of COVID-19, the number of deaths from cardiac disease is rising. Due to advancements in healthcare infrastructure, the mortality rate from heart disease is trending downward in emerging nations. Age, serum creatinine, and serum sodium were significant according to the Chi-square test utilised in this investigation. The ANOVA test, in contrast, revealed important variables such as age, creatinine phosphokinase, ejection fraction, and platelets. Due to the low corrected R2 value, analysis using linear regression is not promising. However, the analysis using logistic regression yields rather encouraging results, attaining an accuracy of 87.8 percent with the help of adjusted MAPR2 = 0.392 and Hosmer-Lemeshow p-value > 0.05. This logistic model is built from the risk factor ejection fraction, serum creatinine, serum sodium, age and time to predict mortality for heart failure sufferers.